The Ophryotrocha diadema group (Annelida: Dorvilleidae), with the description of two new species - Paxton, Hannelore; Åkesson, Bertil (Zootaxa, 2011)
This paper reviews a group of hermaphroditic Ophryotrocha species, here designated as the O. diadema group. This informal group is characterised by its unique P-maxillae and paired mammillate rosette glands. The three members of the group are simultaneous hermaphrodites and have the chromosome complement of 2n = 8. As herein defined, the group includes O. diadema, O. alborana sp. nov., and O. birgittae sp. nov.. The three species can be distinguished by the appearance of their eyes and other morphological and reproductive differences. The species are described, and their life table data is presented.